1973
DOI: 10.1021/jf60187a027
|View full text |Cite
|
Sign up to set email alerts
|

Changes in fatty acids in ripening mango pulp (var Alphonso)

Abstract: Oil extracts were isolated from five stages of ripening Alphonso mango pulp and the fatty acid compositions of the extracts were determined by gas-liquid chromatography. Ripening of pulp was found to be associated with an increase in glyceride content, followed by changes in fatty acid composition of the pulp. As the fruit ripens, a de-crease in linoleic acid content and an increase in linolenic acid content, as well as reciprocal dis-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 5 publications
3
37
0
Order By: Relevance
“…For example, some cultivars such as African mango (Sakho et al, 1985), Venezuelan mangoes (MacLeod & de Troconis, 1982), Tommy Atkins (MacLeod & Snyder, 1988b) and Keitt (MacLeod & Snyder, 1985) in Miami, contained ␦-3-carene as the major components. ␦-3-Carene was a major potent aroma factor for green aroma and mango leaf-like aroma in those mangoes, whilst this compound has not been detected in an Indian cultivar, Alphonso (Bandyopadhyay & Gholap, 1973;Engel & Tressl, 1983), or a Sri Lankan (MacLeod & Pieris, 1984) cultivar. A small amount was contained in the yellow Thai mangoes, Keaw, Ok-rong, Choak-anand, and Nam Dokmai (Tamura et al, 2000).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…For example, some cultivars such as African mango (Sakho et al, 1985), Venezuelan mangoes (MacLeod & de Troconis, 1982), Tommy Atkins (MacLeod & Snyder, 1988b) and Keitt (MacLeod & Snyder, 1985) in Miami, contained ␦-3-carene as the major components. ␦-3-Carene was a major potent aroma factor for green aroma and mango leaf-like aroma in those mangoes, whilst this compound has not been detected in an Indian cultivar, Alphonso (Bandyopadhyay & Gholap, 1973;Engel & Tressl, 1983), or a Sri Lankan (MacLeod & Pieris, 1984) cultivar. A small amount was contained in the yellow Thai mangoes, Keaw, Ok-rong, Choak-anand, and Nam Dokmai (Tamura et al, 2000).…”
Section: Resultsmentioning
confidence: 88%
“…These C 6 compounds are probably derived from lipid peroxidation of fatty acids (Bandyopadhyay & Gholap, 1973) and the related compounds. Nine derivatives of C 6 compounds: hexanal, (Z)-3-hexen-1-ol and the esters were identified in the Khieo Sawoei cultivar.…”
Section: Resultsmentioning
confidence: 99%
“…In avocado fruits, 16:0, 16:1, 18:1, and 18:2 fatty acids were determined as dominant acids in all developmental stages. The content of 16:0,18:1, and 18:2 acids decreased from raw to table ripe and increased slightly in fully ripe and then remained low in overripe not more than in fully ripe fruits (Bandyopadhyay & Gholap 1973). Ratovohery et al (1988) identified six fatty acids during fruit development of some avocado fruits, and they quantified 18:1 (n-9) + 18:1 («-7), 16:0, and 18:2 (n-6) as major acids in all stages of development for 'Lula', 'Bacon', 'Fuerte', and 'Zutano' cultivars.…”
Section: Resultsmentioning
confidence: 87%
“…'Alphonso') fruit. As the pulp ripens a considerable decrease in linoleic acid and a subsequent increase in linolenic acid was observed, whereas the level of oleic acid remained unchanged during this period (Bandyopadhyay & Gholap 1973).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation